The Impact of Time Pressure, Audit Fees and Auditor Motivation on Audit Quality. - Ishak, Parmin; Shalehah, Nur Lazimatul Hilma (Manunggal Halim Jaya, 2022)
This study aimed to empirically investigate the effect of time constraints, audit fees, and auditor motivation on audit quality, either alone or concurrently. The census sampling approach was used to select a sample of 50 independent auditors who work at the Representative Office of the Financial and Development Supervisory Agency (BPKP) in South Sulawesi Province. The data collection instrument was a questionnaire submitted directly to the auditor by the researcher. Multiple regression analysis with the SPSS program was employed as the analytical method in this investigation. Primary and secondary data sources are used in the research. Primary data were gathered through a questionnaire administered by the researcher to the respondents. Secondary data was gleaned from documents pertinent to the subject of the study. This technique was used since there are multiple independent variables. According to the findings of this study, time constraints and auditor motivation have a favorable and significant effect on audit quality. In comparison, audit fees have a significant detrimental impact on audit quality. The findings of this study serve as a guide and motivator for BPKP Auditors as they conduct audits of all government agencies, ensuring that the final reports are of the highest quality. Additionally, researchers can use the findings of this study to contribute insight and serve as a source of reference and information for future research.